Evaluation of oil spill physical processes in the marine environment - Nguyen, Quoc Trinh; Nguyen, Minh Huan; Phung, Dang Hieu; Nguyen, Quang Vinh (Petrovietnam Journal, 2015)
The article introduces some evaluation of oil spill physical processes in the marine environment under the discrete modelling method on the basis of considering the physical processes such as advection, diffusion, upright scrambling and random walk. Based on the most popular formula in the world and comparing results and analysis data, the authors have developed appropriate equations to simulate the physical processes, calculate the coefficients, and parameterise the physical processes affecting the oil spill and the random interaction process of spilled oil.